Pengaruh Covid-19 dan Minat Kuliah Terhadap Penerimaan Mahasiswa Baru (Studi Kasus Akpar Medan Hotel School) - Riza Afni (Cattleya Darmaya Fortuna, 2021)
Covid-19 which has hit the world has made Indonesians experience the impact of termination of employment. Termination of employment results in many people who no longer have regular income every month. For parents who have children who have completed their high school education at the same level, of course, they will think twice about continuing their children's education to tertiary institutions due to economic conditions. Besides that, there are also parents who are very enthusiastic about continuing their children's education to a higher level, even though the economy is not sufficient because education has become one of the necessities of life. This research is located at Akpar Medan Hotel School by taking a sample of 30 prospective students who wish to register as new students. Performed with the multiple linear regression method where X1 is Covid-19 X2 is Study Interest and Y is Student Admission. From the results of the research, the authors found that the influence of Covid-19 in terms of layoffs (Termination of Employment) affects student admissions at Akpar Medan Hotel School which has decreased in the 2020/2021 academic year. However, interest in studying did not affect the decline in student admissions. Simultaneously both of them have an effect on the decrease in the number of new student admissions at Akpar Medan Hotel School.